LOBE-SPECIFIC METASTASIS IN NON-SMALL CELL LUNG CANCER - A. A. Aksarin; M. D. Ter-Ovanesov; A. A. Mordovsky; S. M. Kopeyka; P. P. Troyan (Сибирский онкологический журнал)
Aim: to identify the pathways of lymph node metastases in non-small cell lung cancer (NSCLC).Material and Methods. The frequency of mediastinal lymph node metastases and treatment outcomes were analyzed in 327 patients with stage I–III non-small cell lung carcinoma (NSCLC), who underwent lung resection with systematic lymph node dissection (SLND) between 2007 and 2011.Results. In cases with tumor location in any lobe of the right lung, metastasis occurred in the superior and inferior mediastinal lymph nodes. In left-side tumors, the main pathways of lymphatic spread of tumors were superior and inferior mediastinal nodes as well as aortic lymph nodes. Left lower lobe tumors metastasized most often to inferior mediastinal lymph nodes. Skip metastases were observed at any location of the tumor. Routine examination of all ipsilateral mediastinal lymph nodes overstaged NSCLC in 19.5 % of cases. The overall 5-and 10-year survival rates in patients with stage I–III NSCLC with SND were 61.5 % and 49.2 %, respectively. The median survival time was 103 months.Conclusion. Despite typical metastatic patterns of mediastinal lymph nodes in patients with NSCLC, non-specific metastasis was observed at any location of the tumor, which required mandatory systematic nodal dissection.